Quantifying behavioral biasness in investment decisions with special reference to Uttar Pradesh - Agarwal, A.; Sushma (International Journal of Accounting & Business Finance, 2022)
Behavioral biases haven't gotten the attention they merit, especially in the Indian context. Despite the abundance of information on behavioural finance, only a few academic research has sought to examine behavioural biases across different demographic groups. This research tries to address this lacuna in the literature. The present research work aims to investigate and quantify the behavioural biases that influence individual investors' investment decisions. The primary data was collected through a structured questionnaire from five prominent cities in the most populated state of India, i.e., Uttar Pradesh. The data was collected from 487 individual investors with the help of their financial advisors and brokers. The empirical research work revealed that eight listed biases affect investment decisions by nearly 82%. The outcome as a formal bias assessment instrument was supported by exploratory factor analysis (EFA) encompassing eight behavioural biases measured via 47 statements. The present research contribution, provides a formal assessment tool and further helps the researchers to uncover behavioral biases and develop de-biasing strategies. Academicians, financial advisers, practitioners, and economic psychologists are invited to utilize the instrument in order to further confirm its efficacy.
Keywords: Behavioral Biases; Exploratory Factor Analysis (EFA); Investment Decisions